DIVERSITY OF RICE LEAF PHILOSPHERE BACTERIA AS BIOCONTROL AGENT PATOGEN Pyricularia oryzae, CAUSE OF BLAS DISEASE - Yaskur, Yaskur; Rianto, Fadjar; Syahputra, Edy (Jurnal Sains Mahasiswa Pertanian, 2018)
ABSTRACTRice (Oryza sativa L.) is one of the world's major food crops. Its used as food most for almost all Indonesian people. Productivity of rice plants tend to fluctuate, one of them caused by Pyricularia oryzae. It caused as leaf blast or blast disease on rice. The aim of this research is to get the rice phyllosphere bacteria which possibly have potential as the biocontrol agent to P. oryzae. This research was conducted at Plant Disease Laboratory Faculty of Agriculture, University of Tanjungpura Pontianak. The study was divided into three term, which were leaf sampling, microbial isolation and antagonism testing. There were found 21 isolates of rice leaf filosphere bacteria, there were 12 isolates have capability to decrease growth of pathogens, and 14 isolates had chitinolytic activity. The 5 isolates as a superior biocontrol agent were not as plant pathogenic based on HR test om tobacao.Keywords: Antagonism, Exploration, Fhyllosphere, Chitinolytics.